2001
DOI: 10.1523/jneurosci.21-01-00300.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Auditory–Visual Stimulus Onset Asynchrony Detection

Abstract: Intersensory temporal synchrony is an ubiquitous sensory attribute that has proven to be critical for binding multisensory inputs, sometimes erroneously leading to dramatic perceptual illusions. However, little is known about how the brain detects temporal synchrony between multimodal sensory inputs. We used positron emission tomography to demonstrate that detecting auditory-visual stimulus onset asynchrony activates a large-scale neural network of insular, posterior parietal, prefrontal, and cerebellar areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
241
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(259 citation statements)
references
References 28 publications
18
241
0
Order By: Relevance
“…In some previous studies, as in the case presented herein, the bilateral pSTS particularly failed to respond to congruency manipulation (Bushara et al, 2001;Miller and D'Esposito, 2005;Ojanen et al, 2005). In addition, other studies found a higher BOLD response to the incongruent condition vs. the congruent condition (Benoit et al,2010 ;Pekkola et al, 2006), or vice versa (Calvert et al, 2000;van Atteveldt et al, 2004;van Atteveldt et al, 2009; note that Calvert et al found only left pSTS activation).…”
Section: Congruency Effectssupporting
confidence: 57%
“…In some previous studies, as in the case presented herein, the bilateral pSTS particularly failed to respond to congruency manipulation (Bushara et al, 2001;Miller and D'Esposito, 2005;Ojanen et al, 2005). In addition, other studies found a higher BOLD response to the incongruent condition vs. the congruent condition (Benoit et al,2010 ;Pekkola et al, 2006), or vice versa (Calvert et al, 2000;van Atteveldt et al, 2004;van Atteveldt et al, 2009; note that Calvert et al found only left pSTS activation).…”
Section: Congruency Effectssupporting
confidence: 57%
“…3). This system affords the possibility of potential future studies of cross-modal integration both behaviorally and neurophysiologically, topics that have received increased attention of late (5,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Atteveldt et al (2006) varied temporal alignment plus semantic congruency between visual letter symbols and auditory phonemes, reporting effects in anterior STS, but their paradigm did not assess crossmodal relationships in rapid temporal patterning (i.e., their letters did not correspond in temporal structure to their speech sounds). Several previous imaging studies (Bushara et al, 2001;Bischoff et al, 2007;Dhamala et al, 2007) used tasks explicitly requiring subjects to judge temporal audiovisual (a)synchrony versus some other task but may thereby have activated task-related networks rather than stimulus-driven modulation as here. Although our results converge with a wide literature in implicating human STS in audiovisual interactions, they go beyond this in showing specifically contralateral activations, determined solely by audiovisual temporal correspondence for nonsemantic stimuli, while identifying interregional functional coupling.…”
Section: Activation Of Contralateral Human Msts By Audiovisual Tempormentioning
confidence: 99%